Socially Responsible Human Resource Management and Turnover Intention Relations: Does Employer Brand Matter? - Eser, Hazal; Kalemci Tüzün, İpek (International Journal of Contemporary Economics and Administrative Sciences, 2021)
Since high employee turnover rates have emerged as one of the main problems in the tourism sector, the aim of this paper is to examine the relationship between socially responsible human resource management (SR-HRM), employer brand and employee turnover intention. The paper also aims to investigate whether employees’ employer brand perceptions moderate the relationship between SR-HRM and turnover intentions. An empirical study is conducted on hospitality sector. Quantitative research method is used by collecting questionnaires from 209 employees working in five-star hotels in Turkey. Based on the structural equation modelling the results of the study indicated that SR-HRM practices influenced employees’ turnover intentions. Furthermore, interpreted organizational identity image (IOII), which is considered a sub-dimension of employer brand in the study, has a moderate effect on the relationship between the SR-HRM perceptions of employees and their turnover intentions. Major contribution of this research is that there is limited amount of research is available attempting to measure employer brand perceptions and considering the employer brand as moderating variable in the SR-HRM practices and employees’ turnover intention link as well.